Production of natural dye extracted from jambolan (Syzygium cumini) (Research, Society and Development, 2021)
Among the existing fruits in Brazil, jambolan has stood out for being rich in several beneficial components to health, such as phenolic compounds, and for having antioxidant and antimicrobial properties. Still considering aspects related to health, there is a tendency for consumers to use natural dyes instead of artificial ones. Therefore, the present work had as objective the chemical, physical and technological evaluation of the lyophilized jambolan pulp and the natural dye from the jambolan. To obtain the lyophilized pulp, the pulp was dried in an industrial freeze dryer. Then, the dye was added by means of extraction using water/ethanol (50:50 ratio), and later correction using rice flour as a vehicle, and drying at 30 ° C. The characterization of lyophilized jambolan pulp and natural dye in jambolan powder was carried out by determining the physical-chemical properties, proximal composition, bioactive compounds, water absorption index (IAA), water solubility index (ISA), oil absorption index (IAO), the property of index paste (RVA), calorimetric study (DSC) and electronic research microscopy. The results showed that the dye extraction and correction process increased the percentage of free radical scavenging (6.4) and paste temperature (95.1 ºC), being a thermally stable dye when compared to the lyophilized pulp. We conclude that it is possible to use lyophilized jambolan pulp for the production of natural jambolan dye and application in food.